Value of Sports in Culture Anak Dalam Ethnic National Parks Bukit Duabelas Sarolangun Jambi Province (Case Study Anak Dalam Ethnic in Bukit Suban Village) (Journal of Physical Education and Sports, 2018)
To discuss culture, there is a scope of understanding the form and content of culture that has been clearly explained by Soekanto (2007) about universal cultural elements, as follows: (1) tool and equipment, (2) livelihood, (3) social system, (4) language, (5) art, (6) knowledge system, (7) religion. The research design is a plan and structure is descriptive qualitative research. Data collection techniques use triangulation and with (1) data reduction, (2) data presentation, (3) conclusions. The results of this study: (1) the value of sports in culture associated with tools and equipment, (2) the value of sports in culture related to livelihoods, (3) the value of sports in culture related to social systems, (4) the value of sports in culture related to language, (5) the value of sports in culture related to art, (6) the value of sports in culture related to knowledge systems, (7) the value of sports in culture related to religion. Conclusion: that the value of sports in culture is related to 7 elements of culture Anak Dalam ethnic so much to study and analyze the implications of this research can add information and insight. Suggestions for the local government must pay more attention to the existence of Anak Dalam ethnic.